2195. Effectiveness of a Dual-Test Strategy and Software Modifications for Mitigating and Preventing Hepatitis B Virus (HBV) Exposures in a Dialysis Unit. (26th November 2018) - Lesho, Emil; Hix, John Kevin; Bronstein, Melissa; Shastry, Shubha; Pettis, Margaret; Scroggins, Gina; Vore, Kelly; Grieff, Marvin
Abstract: Background: Yearly, the number of U.S. patients needing dialysis increases by 5%. Unlike patients infected with Hepatitis C or HIV who require only standard precautions during dialysis, patients with HBV infection must be segregated. Given the prevalence of HBV, first time dialysis patients could be infected with HBV and inadvertently dialyzed in a nonsegregated setting, especially if dialysis is urgent. Following such an event, we sought to minimize subsequent exposure risk to roommates of the exposed patients if/when they seroconverted before their serology and HBV-DNA results were available. The high volume of patients needing dialysis, and limited resources, made segregating all exposed for 6 months logistically impossible. We also optimized a widely used electronic medical software program to prevent future incidents. Methods: An exposure was defined as any non-immune patient concurrently dialyzed in the same room with the index case (horizontal; n = 4) or dialyzed on the same machine that was cleaned (but not bleached and heat treated) immediately after the index patient (vertical; n = 1). All received HBV vaccine and immunoglobulin, and all of the dialysis machines were sequestered, bleached, and heat treated after each dialysis. All patients were monitored for seroconversion (SCV) with weekly HBSAg and DNA. The dialysis position of the vertical exposure was moved to last of the day. Root causes of a patient's serologic status escaping verification included: (1) having only a single manual verification step; (2) gaps in a popular medical software (Epic Verona, WI); (3) urgent initiation of the first dialysis session; and (4) automatic importing of lab results. A highly visible "HBV" column on the dialysis census and a"hard stop' in electronic ordering were added. Results: At 1-year follow-up, there were no questions of false-positives, no HBV DNA detections, SCVs, or further incidents. Conclusion: We used both DNA and HBSAg for monitoring the exposed, because using only DNA would have risked missing an inter-dialysis SCV due to its 4-day turnaround time. Although HBSAg can be falsely positive from vaccination, results were available in ≤ 24 hours. As there are no specific recommendations for optimum SCV monitoring and mitigating this type of event, others may find our approach useful. Disclosures: All authors: No reported disclosures.